Championship in Rio de Janeiro city’s ancient stadiums: Bread and Circus before FIFA’s pattern (ARQUISUR Revista, 2014)
The football is one of the most popular sports in Brazil. However, it was in Rio de Janeiro that it was built the most known stadium of the world: Maracanã. This article will discourse about the carioca stadiums and the relation with its neighborhood. Some aspects like its architectonic appearance, public capacity will be evaluated to explain how these aspects produced negative or positive transformations to local area.
Keywords: Rio de Janeiro; sporting architecture; stadiums.